A split-type structure of Ag nanoparticles and Al2O3@Ag@Si nanocone arrays: an ingenious strategy for SERS-based detection. Issue 7 (8th January 2020) - Wang, Zhen; Zheng, Chunxue; Zhang, Peng; Huang, Zhulin; Zhu, Chuhong; Wang, Xiujuan; Hu, Xiaoye; Yan, Jian
Abstract : A split-type nanostructure based on an ordered array and Ag nanoparticles was fabricated as an SERS substrate with high-density SERS hot spots, which exhibited excellent detection signal reproducibility and chemical stability. Abstract : Herein, we report a facile strategy of combined SERS measurements based on a split-type SERS substrate, which exhibits excellent SERS activity, detection signal reproducibility and chemical stability. The SERS substrate consists of an ordered Al2 O3 @Ag@Si nanocone array and Ag nanoparticles (Ag-NPs), both of which are fabricated individually. The Al2 O3 @Ag@Si nanocone array is obtained by ion-sputtering Ag on an Si nanocone array and then coating an ultrathin (∼2 nm) Al2 O3 dielectric layer via atomic layer deposition (ALD). Ag-NPs are synthesized via the liquid phase method and then immersed in an organic solvent for liquid seal. For the SERS measurement, Ag-NPs are dispersed in a liquid containing the probe molecules and then, they self-assemble on the surface of the Al2 O3 @Ag@Si nanocones. Subsequently, the ultrathin Al2 O3 dielectric layer separates Ag-NPs from the Ag@Si nanocones, forming massive gap-introduced hot spots. This substrate is sensitive to 1 pM Rhodamine R6G with an average enhancement factor of up to 10 9, exhibiting excellent SERS activity. Moreover, due to the protection of the Al2 O3 dielectric layer and the organic solvent for the Ag@Si nanocones and Ag-NPs against oxidation, the split-type SERS substrate achieves an SERS signal with almost no attenuation after five months, indicating its good chemical stability.